2013
DOI: 10.4103/0974-8520.115449
|View full text |Cite
|
Sign up to set email alerts
|

Repeated dose oral toxicity of Trivanga Bhasma in Swiss albino mice

Abstract: Trivanga Bhasma, a metallic preparation containing Bhasmas of Naga (lead), Vanga (tin) and Yashada (zinc), was studied for repeated dose toxicity in Swiss albino mice to estimate No Observed Effect Level (NOEL) or No Observed Adverse Effect Level (NOAEL). A total of 80 Swiss albino mice of either sex with an average body weight of 28-30 g were equally divided into four groups (Group I, II, III, and IV). Group I served as control and was given vehicle (honey: water in 2:3 ratio) Group II, III, and IV received T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 3 publications
(4 reference statements)
0
7
0
Order By: Relevance
“…Shodhita Tamra is safer than Ashodhita Tamra , indicating the importance of Shodhana in Bhasma preparation [ 38 ]. In another study, mice were given orally Trivanga Bhasma (Pb, Sn and Zn) at 1, 5, and 10 TED dose daily for 90 days, and no overt abnormal changes in the body weight, feed and water consumption, hematology, and histopathological parameters were observed [ 96 ]. In mice chronically dosed with the Tibetan medicine Zuotai for 135 days at the clinical dose, no abnormality in behavior and overt histopathology occurred.…”
Section: Chemical Forms Of Metals Are a Major Determinant To Theirmentioning
confidence: 99%
“…Shodhita Tamra is safer than Ashodhita Tamra , indicating the importance of Shodhana in Bhasma preparation [ 38 ]. In another study, mice were given orally Trivanga Bhasma (Pb, Sn and Zn) at 1, 5, and 10 TED dose daily for 90 days, and no overt abnormal changes in the body weight, feed and water consumption, hematology, and histopathological parameters were observed [ 96 ]. In mice chronically dosed with the Tibetan medicine Zuotai for 135 days at the clinical dose, no abnormality in behavior and overt histopathology occurred.…”
Section: Chemical Forms Of Metals Are a Major Determinant To Theirmentioning
confidence: 99%
“…Trivanga bhasma (TB) is a metallic preparation containing bhasmas of Naga , Vanga , and Yashada , i.e., lead, tin, and zinc, respectively ( Jamadagni et al, 2017 ). Sprague Dawley rats were injected with streptozotocin (STZ) to induce diabetes followed by dosing of drugs (TB with herbal ingredients (bhawna) and without herbal ingredients) in a human equivalent therapeutic dose i.e., 200 mg/kg for 30 days.…”
Section: Methodsmentioning
confidence: 99%
“… 62 Similarly, toxicity study of Naga Bhasma and Trivanga Bhasma which contains Lead also showed no toxicity in rats for up to the treatment concentration 60 and 78 mg/kg, respectively. 23 , 24 However, administration of higher than therapeutic dose of Tamra Bhasma for 28 days to rats showed mild toxicity in kidney, liver, thymus and heart. 49 On the other hand, few case reports claim that Bhasma has toxic effects due to higher concentration of metals.…”
Section: Use Of Plant Products and Metals In Bhasmamentioning
confidence: 99%
“… 22 , 23 The biocompatibility of Bhasma has been demonstrated in recent studies. 24 , 25 The metals showed toxic effects when present in macro size and showed medicinally beneficial effects when present in micro or nano size. 26 The need for repeated washing, drying and puta steps makes the process of Bhasma preparation time consuming.…”
Section: Introductionmentioning
confidence: 99%